2020
DOI: 10.1088/1755-1315/473/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

The allocation of special autonomy funds and their impact on regional economic inequality in Papua Province

Abstract: Allocation of Special Autonomy Funds and Their Impacts on Regional Economic Inequality (Case Study in Papua Province in 2010-2018). This study aimed to determine the impact of the allocation of special autonomy funds in the field of regional economic inequality both directly and indirectly through the human development index in Papua Province. The type of data used was panel data and data collection was done by the documentation method. The data were analyzed using the Simultaneous Equation Model approach with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Meanwhile, the special autonomy fund for community economic empowerment has no real impact on regional economic disparities. Special autonomy financing factors in the fields of education, health, infrastructure, and community economic empowerment do not have a major effect on regional economic disparities if measured indirectly through HDI (Tamberan et al, 2020).…”
Section: Resultsmentioning
confidence: 91%
“…Meanwhile, the special autonomy fund for community economic empowerment has no real impact on regional economic disparities. Special autonomy financing factors in the fields of education, health, infrastructure, and community economic empowerment do not have a major effect on regional economic disparities if measured indirectly through HDI (Tamberan et al, 2020).…”
Section: Resultsmentioning
confidence: 91%
“…Supporters often justify it as a means to expedite welfare improvements, while opponents perceive conflicting interests and fear it will introduce new challenges in the expanded areas. For example, special autonomy in Papua, followed by special autonomy funds, has not effectively reduced economic inequality in Papua (Tamberan et al, 2020). This raises questions about the validity of the welfare narrative.…”
Section: Mapping the New Autonomous Region That Will Become The New P...mentioning
confidence: 99%
“…Then, another study by (Tamberan et al, 2020) which looked at the impact of the allocation of Special Autonomy Funds in the fields of education, health, infrastructure, and community economic empowerment on regional economic inequality, both directly and indirectly through HDI in Papua in 2010-2018. The results showed that the Special Autonomy Fund variables in education and health had a significant positive effect on HDI, while the Special Autonomy Fund variables in infrastructure and community economic empowerment did not have a significant effect on HDI.…”
Section: Graphs 1 Total Allocation Of Special Autonomy Funds Per Fiel...mentioning
confidence: 99%